Saints and warriors strategic choice in rebel recruitment in the Syrian civil war - Albrecht, Holger 1972- (2022)
This article explores how rebel groups come into being and how they sustain their activities. Its core premise is that the strategies used in rebel recruitment are crucial for such organisations. Knowing how rebel groups attract members will tell us why they are strong and, by extension, who is getting the upper hand in violent domestic conflicts. Drawing on empirical findings from the Syrian civil war, the article unpacks strategic choices in rebel recruitment: successful rebel groups benefit from the recruitment of combat-ready fighters (warriors) at the time of their inception and of high-commitment rebels (saints) amid sustained insurgent activities.
Literaturverzeichnis: Seite 406-410
Keywords: Bürgerkrieg; Miliz; Rekrutierung; Militär; Personalpolitik; Strategische Planung; Einrichtung; Organisationsstruktur; Syrien